2009
DOI: 10.2174/187152809788681038
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anaphylatoxins C3a and C5a in Regulating Innate and Adaptive Immune Responses

Abstract: C3a and C5a, the small (approximately 10KDa) cleavage fragments released by complement activation, are potent mediators of inflammation. They are anaphylatoxins and act as cell activators with nanomolar affinity, exerting their functions through binding to specific receptors (C3aR and C5aR or C5L2 respectively). Recent studies suggest that locally generated complement effector molecules including C3a and C5a contribute to pathological processes in inflammatory and immunological diseases as well as adaptive imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
107
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 100 publications
1
107
0
Order By: Relevance
“…The presence of correlation between PMNE and Bb levels point to the initiation of alternative amplification loop extending complement activation. Complement activation attracts and activates neutrophils [31,32], and in turn may exacerbate NET release, initiating a positive feed-back loop. These observations are in line with the recent report on the association among circulating nucleosomes, activated neutrophils (as indicated by increased neutrophil elastase-α1-antitrypsin complexes), and presence of deep vein thrombosis [33].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of correlation between PMNE and Bb levels point to the initiation of alternative amplification loop extending complement activation. Complement activation attracts and activates neutrophils [31,32], and in turn may exacerbate NET release, initiating a positive feed-back loop. These observations are in line with the recent report on the association among circulating nucleosomes, activated neutrophils (as indicated by increased neutrophil elastase-α1-antitrypsin complexes), and presence of deep vein thrombosis [33].…”
Section: Discussionmentioning
confidence: 99%
“…C1q deficiency causes a defect in the clearance of apoptotic cells (33), reduces B cell tolerance to intracellular Ags (34), and predisposes patients to autoimmune disease. Complement C3a is a small 7-kDa protein generated by C3-convertase during complement activation through the classical pathway, MB-lectin pathway, or alternative pathways (35). C3a is one of most potent mast cell chemoattractants and induces mast cell degranulation (36).…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition to their role in innate immunity, several effector molecules including C3a and C5a have been shown to regulate adaptive immunity through activation of their receptors on immune cells. 2,3 The small fragments C3a, C4a, and C5a released by complement activation are anaphylatoxic peptides. Of these mediators, C5a has the highest specific biologic activity.…”
mentioning
confidence: 99%
“…4 Expression of C5aR has been reported in many cell types including both myeloid and nonmyeloid cells. 2,4 It is well known that engagement of the receptor on several myeloid cells (e.g., neutrophils, monocytes/macrophages, and mast cells) leads to the induction of local inflammation through a process of cellular degranulation, increased vascular permeability, and leukocyte recruitment to the site of injury/infection, whereas engagement of the receptor on parenchymal cells (e.g., endothelial cells and epithelial) lead to cell activation and functional modulation. 4 Although C5a-induced inflammation plays an important role in the host defense, many studies have shown that C5a can also cause undesired inflammatory responses that contribute to the pathogenesis of several inflammatory diseases such as sepsis, asthma, and ischemia/reperfusion injury.…”
mentioning
confidence: 99%